Kinematic Differences Between the Front and Back Squat and Conventional and Sumo Deadlift. Issue 12 (December 2019) - Kasovic, Jovana; Martin, Benjamin; Fahs, Christopher A.
Abstract : Abstract: fferences between the front and back squat and conventional and sumo deadlift. J Strength Cond Res 33(12): 3213–3219, 2019—The average concentric velocity (ACV) of a resistance exercise movement is inversely related to the load lifted. Previous work suggests that different resistance exercises differ in ACV at the same relative load. Currently, there is limited evidence to determine whether the style of exercise (e.g., front or back squat [BS]; sumo-style or conventional-style deadlift) also affects the load-velocity profile or other kinematic variables such as the peak concentric velocity (PCV) and linear displacement (LD). The purpose of this study was to compare the kinematics (ACV, PCV, and LD) between the front squat (FS) and BS as well as between the conventional deadlift (CD) and sumo deadlift (SD). In a randomized order, 24 men and women (22 ± 3 years) performed a 1 repetition maximum (1RM) protocol for the FS, BS, CD, and SD over 4 visits to the laboratory. Barbell kinematics were recorded during all submaximal and maximal repetitions performed during the 1RM protocol using the Open Barbell System. Kinematic data were pooled into categories based on the percentage of the 1RM lifted in 10% increments (e.g., 30–39% 1RM, 40–49% 1RM, etc.) and compared between exercises. Correlations between kinematic data for the FS and BS and for the CD and SD were examined at each relative load. No differences in kinematics were observed between the FS and BS at any load ( p > 0.05). However, FS and BS ACV was weakly correlated ( r < 0.4) at high (>80% 1RM) loads. Differences in LD were apparent between the SD and CD at all loads (30–100% 1RM) with the SD having a smaller LD compared with the CD ( p < 0.05). Average concentric velocity was not different between the SD and CD at the 1RM (0.25 ± 0.09 vs. 0.25 ± 0.06 m·s −1 ; p = 0.962) but was different at 80–89% 1RM (0.35 ± 0.08 vs. 0.40 ± 0.07; p = 0.017), 70–79% 1RM (0.41 ± 0.08 vs. 0.46 ± 0.06; p = 0.026), and 40–49% 1RM (0.66 ± 0.09 vs. 0.77 ± 0.08; p < 0.001). In addition, SD and CD ACV values showed no relationships ( p > 0.05) at any loads except at the 1RM ( r = 0.433; p < 0.05). These results suggest individual load-velocity profiles for the FS and BS as well as for the CD and SD should be used for training purposes.